Characteristics of polycystic ovary syndrome throughout life - Yvonne V. Louwers; Joop S.E. Laven (Therapeutic Advances in Reproductive Health, 2020)
Polycystic ovary syndrome is the most common endocrine disorder in women of reproductive age. It is a complex disease in which genetic, endocrine, environmental, and behavioral factors are intertwined, giving rise to a heterogeneous phenotype with reproductive, metabolic, and psychological characteristics. Polycystic ovary syndrome affects women’s health and their quality of life across the life course. During different life stages, the polycystic ovary syndrome phenotype can change, which requires a personalized diagnostic approach and treatment. Polycystic ovary syndrome is a major cause of anovulatory infertility; this disorder is also associated with hirsutism and acne. Diagnosing polycystic ovary syndrome during adolescence is challenging because the polycystic ovary syndrome criteria include normal physiological events that occur during puberty. With increasing age, the syndrome evolves from a reproductive disease to a more metabolic disorder. Along with metabolic disturbances, including insulin resistance and abnormalities of energy expenditure, polycystic ovary syndrome is recognized as a major risk factor for the development of type 2 diabetes and cardiovascular disease in later life. Moreover, there is evidence for familial clustering of endocrine and metabolic features of polycystic ovary syndrome. Environmental factors such as diet and obesity appear to contribute to the phenotype. Treatment should be tailored to the specific concerns and needs of the individual patient and involves restoring fertility, treatment of the metabolic complaints, treatment of androgen excess, and providing endometrial protection. The complexity of the disorder, and the impact on quality of life, requires a timely diagnosis, screening for complications, and management strategies for the long-term health issues associated with polycystic ovary syndrome. The syndrome remains underdiagnosed, and women experience significant delays to diagnosis.